2009
DOI: 10.1007/s10195-009-0047-5
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum OPG in atrophic nonunion shaft fractures

Abstract: BackgroundBone repair alteration is hypothesized for nonunion fracture pathogenesis. Since it is involved in osteoclast regulation, the RANK/RANKL/OPG system (receptor activator of nuclear factor kB/its ligand/osteoprotegerin) may play a role.Materials and methodsSerum OPG, free RANKL, bone alkaline phosphatase (BAP), osteocalcin (OC), and urinary deoxypyridinoline (DPD) were determined in 16 male patients (20–39 years) with long bone atrophic nonunion fractures. Serum markers were also measured in 18 age-matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 11 publications
1
30
1
Order By: Relevance
“…There are few reports about the modes of action of RANKL, OPG and none about RANK during fracture healing in humans. In these studies, following patients with fractures at different anatomical sites, no differences have been shown in these biological measurements between upper and lower limb [14,15]. Our study represents one of the first investigations to define the involvement of RANK, RANKL and OPG in fracture healing and their possible roles as biomarkers to monitor this process.…”
Section: Discussionmentioning
confidence: 76%
“…There are few reports about the modes of action of RANKL, OPG and none about RANK during fracture healing in humans. In these studies, following patients with fractures at different anatomical sites, no differences have been shown in these biological measurements between upper and lower limb [14,15]. Our study represents one of the first investigations to define the involvement of RANK, RANKL and OPG in fracture healing and their possible roles as biomarkers to monitor this process.…”
Section: Discussionmentioning
confidence: 76%
“…In the first study, lower OC concentrations were reported in the group of patients whose fractures evolved into delayed union than in the group showing normal bone union, from the first days after treatment and throughout the entire study period, while in the second study there was a lag in the rise of OC concentration during the first 2 months amongst the group of patients that underwent a delayed union. Nevertheless, Emami et al (1999) and Marchelli et al (2009) found that serum OC concentration was unable to differentiate between a delayed union and a normal bone union. These studies present some limitations that could call into question the comparability of the results from the different study groups, results which are mainly related to the small number of patients included in each group.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to molecules that regulate the function of osteoclasts, a preliminary clinical study was conducted in which differences were observed in serum OPG levels between patients who had developed an atrophic non-union and those that had progressed towards normal fracture healing (Marchelli et al 2009). However, in a more recent study, it was noticed that in patients with a normal bone-union, serum OPG, RANK and RANKL levels were not affected by the fracture healing process, since these levels remained unchanged (2005) verified that the serological variation of TGF-β1 could contribute to an early detection of an impaired fracture healing process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 There is clear motivation to increase drug delivery to bone, as approximately 6 million bone fractures occur annually in the United States, of which nearly 20% result in non-unions or delayed unions. 21 Impaired healing is due to dysfunctions in bone remodeling, including poor vascularization, 2224 overactive osteoclasts, 25 and deficient osteoblasts. 26–28 A variety of drugs have great potential for overcoming these deficiencies.…”
Section: Introductionmentioning
confidence: 99%